Molecular Engineering of Photoacoustic Performance by Chalcogenide Variation in Conjugated Polymer Nanoparticles for Brain Vascular Imaging - Liu, Jie (WILEY-V C H VERLAG GMBH, 2020)
10.1002/smll.201703732